Women are more sensitive than men to prior trial events on the Stop‐signal task. (15th May 2013) - Thakkar, Katharine N.; Congdon, Eliza; Poldrack, Russell A.; Sabb, Fred W.; London, Edythe D.; Cannon, Tyrone D.; Bilder, Robert M.
<x xml:space="preserve">Abstract</x> Sexual dimorphism in the brain and cognition is a topic of widespread interest. Many studies of sex differences have focused on visuospatial and verbal abilities, but few studies have investigated sex differences in executive functions. We examined two key components of executive function – response inhibition and response monitoring – in healthy men (n = 285) and women (n = 346) performing the Stop‐signal task. In this task, participants are required to make a key press to a stimulus, unless a tone is presented at some delay following the initial stimulus presentation; on these infrequent trials, participants are instructed to inhibit their planned response. Response inhibition was assessed with an estimate of the latency needed to inhibit a response (stop‐signal reaction time), and response monitoring was measured by calculating the degree to which participants adjusted their reaction times based on the immediately preceding trial (e.g., speeding following correct trials and slowing following errors). There were no sex differences in overall accuracy or response inhibition, but women showed greater sensitivity to trial history. Women sped up more than men following correct 'Go' trials, and slowed down more than men following errors. These small but statistically significant effects (Cohen's d = 0.25–0.3) suggest more flexible adjustments in speed–accuracy trade‐offs in women and greater cognitive flexibility associated with the responsive control of action.